A rare case of a clinically significant anti-M alloantibody in a heart transplant recipient. (February 2022) - Sharma, Deva; Johnson, Mary; Venable, Josef; Eichbaum, Quentin; Stiefel, Elijah
Abstract: Introduction: Anti-M antibodies are usually inactive at physiologic temperatures (37 °C). Rarely, these antibodies have been reported to react at physiologic temperatures, resulting in clinically significant hemolytic transfusion reactions or hemolytic disease of the fetus and newborn. Patient and methods: We describe a case of an acute hemolytic transfusion reaction due to an anti-M alloantibody reacting at physiologic temperatures in a critically ill patient. Results: Proper identification and management of anti-M antibody-mediated acute hemolysis rapidly improved and stabilized her hemoglobin. Conclusion: Differentiation between anti-M antibody-mediated acute hemolysis and its differential diagnoses is of critical importance to guide therapeutic decisions in these rare clinical scenarios.